Strategy for flexible operation of three-phase converters - Da Luz, Alessandro L. [UNESP]; Paredes, Helmo K. Morales [UNESP]; Bonaldo, Jakson Paulo; Pomilio, Jose Antenor (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper depicts a multifunctional control strategy applied in three-phase inverters, which are connected to the distribution network. The proposed strategy is able to inject active power into the electrical grid and compensate current disturbances simultaneously. The main goal of this flexible strategy is to improve the Power Quality at the point of common coupling allowing full or partial compensation of disturbances. Power factor is the main quality index observed and it is calculated according to Conservative Power Theory. Therefore, based on the power factor measured in the grid side and the desired value for the power factor, a compensation coefficient (k) is calculated continuously adjusting the amplitude of the compensation current.
Keywords: active power filter; power quality; renewable energy source